The new digital storytelling : creating narratives with new media - Alexander, Bryan, ....- (Santa Barbara : ABC-CLIO, 2017)
Newly revised and updated, this is the essential guide to state-of-the-art digital storytelling for audiences, creators, and teachers. * Documents how digital storytelling has become an international movement, with vibrant communities of practice, ever-developing ideas, and growing appeal * Captures the full depth and breadth of the history and present of digital storytelling, while also offering practical tips for getting started making stories * Incorporates a plethora of digital technologies, from video to augmented reality, and mobile devices to virtual reality * Points out that digital storytelling has a variety of uses and encompasses a growing diversity of technologies, even as it becomes ever more accessible to everyday creators
Includes bibliographical references (pages 275-282) and index.
Keywords: Digital storytelling; Interactive multimedia; Storytelling -- Data processing